Mediation as an Alternative to Resolving Inherited Disputes of Congenital Children: Juridical and Economic Perspectives - Arifin, Irvan Zidny; Azizah, Luthfi Nur; Raharjo, Dino Gautman; D, Karmila Sari Aprina; Asnawi, M. Natsir (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2024)
Inherited children have their own problems when examined normatively in terms of inheritance. Juridical law states that rights are equalized between inherited children and heirs. In contrast to both, customary norms actually equalize the share of inherited assets. This is where the role of mediation is as a media consultant and legal mediator who weighs normative, juridical and customary law so that they can find a middle way between these things. This research uses a normative, juridical and economic approach using literature study. The aim of this research is to examine the role of mediation in dealing with customary inheritance which equalizes between inherited children and heirs, then followed by the flow of mediation, both the flow of registration and the costs incurred. There is a continuity between normative, juridical and customary issues related to inheritance, namely the existence of an element of blessing in the distribution of inheritance to heirs, mediation as a middle way that connects these three problems with the flow of registration and the amount of costs incurred. [Abstrak: Anak bawaan memiliki problem tersendiri apabila ditelisik secara normatif dalam hal kewarisan, hukum yuridis mengatakan penyamarataan hak antara anak bawaan dengan ahli waris, berbeda dengan keduanya norma adat justru menyamaratakan bagian harta tinggalan. Disinilah peran mediasi sebagai media konsultan dan penengah hukum yang menimbang antara hukum normatif, yuridis dan adat sehingga dapat menemukan jalan tengah diantara hal tersebut. Penelitian ini menggunakan pendekatan normatif, yuridis, dan ekonomis dengan menggunakan studi kepustakaan. Tujuan penelitian ini adalah untuk meneliti terkait peran mediasi dalam menyikapi kewarisan adat yang menyamaratakan antara anak bawaan dengan ahli waris, kemudian disusul dengan alur mediasi baik itu alur pendaftaran, dan biaya yang dikeluarkan. Terdapat tali kesinambungan antara normatif, yuridis, dan adat terkait kewarisan yakni adanya unsur ridho dari pembagian waris kepada ahli waris, mediasi sebagai jalan tengah yang menghubungakan ketiga problem tersebut memiliki alur pedaftaran dan besaran biaya yang dikeluarkan.]